2023
DOI: 10.1186/s40529-022-00365-6
|View full text |Cite
|
Sign up to set email alerts
|

Living on the edge: morphological, karyological and genetic diversity studies of the Hungarian Plantago maxima populations and established ex situ collection

Abstract: Background The analysis of genetic diversity of protected plant species can greatly support conservation efforts. Plantago maxima Juss. ex Jacq. is a perennial species distributed along the Eurasian steppe. The westernmost range edge of the species’ distribution is located in the Pannonian basin, in Hungary where it is represented by a few, fragmented and highly endangered populations. We studied population diversity of all Hungarian range edge, natural populations, and one established ex situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Accordingly, it is reasonable that the chromosomally diverse distribution of 5S rDNA is visualized by FISH. Previous studies have shown that the numbers of 5S rDNA FISH signal sites range from 1 to 71 [3,12,19,20,69]. Such a signal position was found in the chromosome interstitial position, distal position, proximal position, and far away from the chromosome [3,21,[25][26][27].…”
Section: Occurrence and Diversity Of 5s Rdna In Plantsmentioning
confidence: 89%
“…Accordingly, it is reasonable that the chromosomally diverse distribution of 5S rDNA is visualized by FISH. Previous studies have shown that the numbers of 5S rDNA FISH signal sites range from 1 to 71 [3,12,19,20,69]. Such a signal position was found in the chromosome interstitial position, distal position, proximal position, and far away from the chromosome [3,21,[25][26][27].…”
Section: Occurrence and Diversity Of 5s Rdna In Plantsmentioning
confidence: 89%
“…Because of this, it is quite reasonable that the chromosomally diverse distribution of 5S rDNA is visualized by FISH. Numerous previous studies showed that the numbers of 5S rDNA FISH signal sites ranged from 1 to 71 (Ali et al 2005, Lan and Albert 2011, Luo et al 2017, Kovács et al 2023, Rodríguez-González et al 2023). Their signal position was found in the chromosome interstitial position, distal position, proximal position, and far away from the chromosome (Amarasinghe and Carlson 1988, Cai et al 2006, Campomayor et al 2021, Wang et al 2022, Rodríguez-González et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The lengths of the 5S rDNA sequence ranged from 48 bp (Turner et al 2005) to 854 bp (Liu et al 2017) because of its high copies and variations when searching for “5S rDNA” in the database Nucleotide of National Center for Biotechnology Information. Furthermore, the lengths of 5S rDNA as a FISH probe in the PubMed database from NCBI varied considerably: 41 bp (Luo et al 2017, Islam-Faridi et al 2020), 94 bp (Sergeeva et al 2017), 117 bp (Lukjanová et al 2023), 120 bp (Taketa et al 2001, Symonová et al 2017, Deon et al 2022, de Moraes et al 2023), 124 bp (Waminal et al 2018), 131 bp (Sergeeva et al 2017), 222 bp (Glugoski et al 2018), 285 bp (Röser et al 2001), 300 bp (Araya-Jaime et al 2022), 302 bp (Zhang et al2016), 303 bp (Mahelka et al 2013), 320 bp (Khensuwan et al 2023), 324 bp (Kamisugi et al 1994), 326 bp (Robledo and Seijo 2008), 329 bp (Röser et al 2001), 347 bp, ∼400 bp (Pedrosa et al 2002), 410 bp (Kovács et al 2023), 456 bp (Röser et al 2001), 468 bp, 473 bp, 477 bp, 496 bp (Martins et al 2000), 497 bp (Alexandrov et al 2022), 498 bp (Martins et al 2000), 500 bp (de Barros et al 2023), 556 bp (Gottlob-McHugh et al 1990), 596 bp (Joshi et al 2023), 702 bp (Glugoski et al 2018), 871 bp (Amarasinghe and Carlson 1988), and 1193 bp (Glugoski et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is also accepted that in the time of the Holocene many plant species migrated from the Balkan region towards the Pannonian lowland or reaching the mountain sites of the Carpathians. Recently, evidences were listed supporting the idea that flora of the Carpathian basin might have served as genetic resource of recolonization in the Holocene, as some populations survived the glacial cycles in the Carpathian basin [10]. Studies on both persistence, survival potential and comparative genetics of peripheral and central populations might provide important contribution for species conservation.…”
Section: Introductionmentioning
confidence: 99%